Le poète, le cardinal et l’ange du foyer - Jacqueline Clais (Cahiers Victoriens et Edouardiens)
In 1881 cardinal Manning who supports the Irish farmers in their struggle for more justice is the butt of all sorts of attacks on the part of the protestant but also the catholic landed gentry. Curiously it is an article in the Whitehall Review about a pretended love affair with Marianne Byles, before she was married to Coventry Patmore, which wounds him to the quick. A few letters between the protagonists let us see a very different, much more human aspect of the austere prelate who has not forgotten Caroline “the angel of his house”.